Antibacterial activity of Rosmarinus officinalis and Dodonaea viscosa leaves extracts against Escherichia coli and Staphylococcus aureus - Atala, Mohammed Lefta; Aldabagh, Muhammed Abdul-Gabar (Iraqi Journal of Science, 2021)
The isolates from urine and synovial fluid samples of Escherichia coli and Staphylococcus aureus bacteria were isolated and identified, in order to study alternative treatment or antibacterial agents of plant extracts from Rosmarinus officinalis and Dodonaea viscosa plants. The isolates were identified by using cultural and biochemical tests, in addition to API 20E kit as confirmation test. The results exhibited that Rosemary extract prevents the biofilm formation and causes inhibition to bacterial growth, while the doddonia extract causes antibacterial activity on the tested bacteria.